KEBERHASILAN PRAKERIN KARENA PENGUASAAN MATA DIKLAT PRODUKTIF AKUNTANSI DAN MINAT SISWA DI SMK - Muslimah, (Pendidikan Ekonomi, 2011)
The aim of the study was to examine the effect of the mastery of productive accounting course and interest on the success of industrial internship among the eleventh graders in the accounting program of SMK Negeri I Lamongan. The subjects were 38 eleventh graders of the school.The data were collected through documentation and questionnaire. The data were then analyzed with multiple regressions. The result of the study showed that the studentsmastery of productive accounting course and interest affected their success in industrial internship by 19.4 %, while other variables affected the rest.